If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -8 = -3(x + 2) Reorder the terms: -8 + 6x = -3(x + 2) Reorder the terms: -8 + 6x = -3(2 + x) -8 + 6x = (2 * -3 + x * -3) -8 + 6x = (-6 + -3x) Solving -8 + 6x = -6 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -8 + 6x + 3x = -6 + -3x + 3x Combine like terms: 6x + 3x = 9x -8 + 9x = -6 + -3x + 3x Combine like terms: -3x + 3x = 0 -8 + 9x = -6 + 0 -8 + 9x = -6 Add '8' to each side of the equation. -8 + 8 + 9x = -6 + 8 Combine like terms: -8 + 8 = 0 0 + 9x = -6 + 8 9x = -6 + 8 Combine like terms: -6 + 8 = 2 9x = 2 Divide each side by '9'. x = 0.2222222222 Simplifying x = 0.2222222222
| (x^2-y^2)(y^2-x^2)=9 | | y=4x-16 | | -4x+100=0 | | 16-0,8x=x/3,75 | | 99-6x=39x+19 | | -63-3x=7x-10 | | -63-3x=6x+8 | | 3x^2-1x+5=0 | | 2/(x-1)=5/(x+3) | | 2/x-1=5/x+3 | | 39.8=t/(t+9.4) | | 2x^2+3x-5=10 | | (1/9)x+(1/10)=(11/90) | | (1/9)x+(1/10)+(11/90) | | 5x^8+12x^6+39x^4+48=0 | | -14+(x-17)=-4 | | y=6-6x/7 | | 192=3x-(x-32) | | 1/3x+5/4=7/12x+2 | | 3/2+1/4x=1/2 | | -14-10x=-7x+4 | | 5a+9=34 | | 3(3x+x)+7(x-4)=5 | | -18+6y=10y+30 | | 5/9*40 | | 5/9x40 | | -2t+-2=4-8t | | 0.074-0.26x=0.035-0.14x | | 5x-8=x-20 | | 7+3(2-2x)=9 | | .06x+1.7=-0.44x+3 | | 100/18.75 |